Effect of Pogostemon cablin Aqueous Extract on Gut Barrier in Mouse Model of Ulcerative Colitis - Xin JIN; Nan ZHANG; Xiaoliang MEI; Shihao SUN; Liwen ZHAO; Baofei YAN (Shipin gongye ke-ji, 2024)
Objective: To explore the ameliorative effects and mechanisms of Pogostemon cablin aqueous extract (PCAE) on mice with ulcerative colitis (UC) based on gut barrier research. Methods: Mice were randomly divided into five groups: Control, model, mesalazine, low-dose of PCAE and high-dose of PCAE groups. A UC model was induced in mice by freely drinking 2.5% dextran sodium sulfate (DSS) for 10 d, with simultaneous oral administration of interventions. The study measured levels of serum interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor α (TNF-α). Pathological alterations in the colon were observed using hematoxylin-eosin and periodic acid-schiff staining. The expression of the colonic tight junction proteins zonula occludens-1 (ZO-1), occludin-1, and mucin 2 (MUC2) were assessed via immunohistochemistry. High-throughput sequencing technology was utilized to analyze changes in the gut microbiota of colonic contents. Results: Following intervention with PCAE, DSS-induced mice exhibited a significant reduction in serum levels of IL-6, IL-1β, and TNF-α (P<0.05, P<0.01). Pathological improvements in colon inflammation, epithelial cell structural damage, and reduced goblet cell numbers were observed. Additionally, the expression of colonic ZO-1, occludin-1, and MUC2 proteins significantly increased (P<0.05, P<0.01). Furthermore, the α-diversity indices of the gut microbiota including sobs, Shannon, and heip exhibited a marked increase (P<0.05, P<0.01), while the β-diversity analysis through principal component analysis, principal co-ordinates analysis, and non-metric multidimensional scaling analysis tended towards that of healthy mice. Notably, there was a significant correction in the abundance of dominant species at the genus level, including Romboutsia, Bifidobacterium, Blautia, and unclassified_f__Lachnospiraceae (P<0.05, P<0.01). Conclusion: PCAE exhibited a clear ameliorative effect on DSS-induced UC in mice, potentially achieved through the improvement of the gut barrier.